Minimally invasive surgery and transsulcal parafascicular approach in the evacuation of intracerebral haemorrhage. Issue 1 (26th September 2019) - Marenco-Hillembrand, Lina; Suarez-Meade, Paola; Ruiz Garcia, Henry; Murguia-Fuentes, Ricardo; Middlebrooks, Erik H; Kangas, Lindsey; Freeman, W David; Chaichana, Kaisorn L
Abstract : Intracerebral haemorrhage (ICH) describes haemorrhage into the brain parenchyma that may result in a decline of the patient's neurological function. ICH is a common cause of morbidity and mortality worldwide. Aggressive surgical treatment for ICH has remained controversial as clinical trials have failed to demonstrate substantial improvement in patient outcome and mortality. Recently, promising mechanical and pharmacological minimally invasive surgery (MIS) techniques for the treatment of ICH have been described. MIS was designed with the objective of reducing morbidity due to complications of surgical manipulation. Mechanical MIS includes the use of tubular retractors and small diameter instruments for ICH removal. Pharmacological methods consist of catheter placement inside the haematoma cavity for the passive drainage of the haematoma over the course of several days. One of the most favourable approaches for MIS is the use of natural corridors for reaching the lesion, such as the transsulcal parafascicular approach. This approach provides an anatomical dissection of the subjacent white matter tracts, causing the least amount of damage while evacuating the haematoma. A detailed description of the currently known MIS techniques and devices is presented in this review. Special attention is given to the transsulcal parafascicular approach, which has particular benefits to provide a less traumatic MIS with promising overall patient outcome.